2017
DOI: 10.17096/jiufd.95254
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Chewing Sensitivity During Fixed Orthodontic Treatment in Extraction and Non-Extraction Patients

Abstract: Purpose:The aim of this study was to evaluate the differences in pain perception and chewing sensitivity between extraction and non-extraction patients.Subjects and Methods:Thirty orthodontic patients (11 males, 19 females) were included in this study who were classified as extraction (n=15; 6 males, 9 females) and non-extraction patients (n=15; 7 males, 8 females). The mean age of patients were 15.10±1.83 years in non-extraction group and 15.44±0.75 years in extraction group. The patients were asked to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Pain perception is associated with age of the patient, pain threshold, motivation, psychological condition, and previous negative dental experience of the patient. [ 5 ] In our study, there was no statistically significant difference between male and females in both untreated and treated groups for pain perception [ Table 1 ]. Our results are in concurrence with results of Kadu et al and Abu Alhaija et al [ 1 2 ] In contrary to our results, Bergius et al observed higher pain perception in females compared to males.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Pain perception is associated with age of the patient, pain threshold, motivation, psychological condition, and previous negative dental experience of the patient. [ 5 ] In our study, there was no statistically significant difference between male and females in both untreated and treated groups for pain perception [ Table 1 ]. Our results are in concurrence with results of Kadu et al and Abu Alhaija et al [ 1 2 ] In contrary to our results, Bergius et al observed higher pain perception in females compared to males.…”
Section: Discussionmentioning
confidence: 66%
“…[ 1 3 4 ] Fear of pain may avoid person from taking treatment or discontinuing the orthodontic treatment. [ 5 ] Ngan et al observed no significant difference between the gender for discomfort, and they observed a decrease in discomfort from initial time to 7 days after appliance insertion. [ 6 ] The main cause of pain during orthodontic treatment is force application to induce tooth movement.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies assessed the change in occlusion and masticatory function post-orthodontic treatment and evaluated the self-perceived masticatory function with tested masticatory efficiency among both treated and untreated groups [25,26]. Thirteen studies evaluated the impact of orthodontic appliances and therapies on masticatory and swallowing functions [1,27], perceived and actual pain sensation [28][29][30], and other related aspects such as oral comfort, speech, and dietary habits [27,[31][32][33][34][35][36][37][38]. Two studies evaluated the masticatory performance and temporomandibular disorders (TMDs) in patients before and after orthodontic and orthognathic treatments [39] and the improvement of the masticatory movement in patients after orthognathic treatment [40].…”
Section: Resultsmentioning
confidence: 99%
“…The strength of this investigation is in the homogenous study group and the possibility to consider maxillary and mandibular teeth as paired samples. It was reported that different archwire sizes 16,24 , bracket type or slot size [25][26][27] , as well as extractions 28 do not influence the pain intensity during the initial orthodontic treatment. Our Self-medication with analgesics after bonding was reported for both maxillary and mandibular teeth, starting with 32% and 44% of patients on day 1, respectively.…”
Section: Resultsmentioning
confidence: 99%